Modification of Sunda Manda Games Based on Theme to Improve Early Mathematic Abilitien in TK Aisyiyah Kindergarten Jenang Village Kecamatan Majenang Cilacap District - Saputro, Widayat; Kurniawati Sugiyo Pranoto, Yuli; Utanto, Yuli (Universitas Negeri Semarang, 2021)
Early childhood certainly does not know about mathematics, therefore the task of PAUD teachers or educators who introduce mathematics. Many teachers are not pleasant in learning or stressing on children, so children will get bored quickly in learning mathematics. Modification of Sundanese Games Manda will answer that, even though some of these traditional children's games are very foreign to the ears of children today. One alternative that can be used is to make a Sundanese Sundanese game modification made of banner material. Thus the modification of Sunda Sunda game is expected to later help improve the ability of early mathematics and is liked by students and the community. The purpose of this study is to describe the implementation of early mathematics learning and describe the modification of the Sundanese Sundanese game based on themes to improve early math skills by classifying objects based on color, shape, type, and size in group B children. The research design used is a qualitative approach. This research is about a case study regarding the modification of Sunda Sunda game based on themes to improve early mathematical abilities. The population of this research is kindergarten children class B (ages 5-6 years) in kindergarten Aisyiyah, Jenang Village. The selected sample is 21 children. The steps in analyzing the data that have been carried out in this study, namely the data in the form of interviews through several questions submitted to the Head of Kindergarten and the Teachers as research informants. The instructors in instilling early mathematical habituation in children about thematic material. In preschoolers, mathematics is only experience and not mastery. Concepts that must be introduced to children by starting; one-to-one correspondence, patterns, sorting / sorting / classifying, numerating, the meaning of numbers and their recognition, shape, size, time and space. Conclusions that can be taken based on the results and discussion stated that 1) Sunda Sundanese game modification based on themes can improve early math skills in group B children in kindergarten Aisyiyah Jenang Village 2) the implementation of early mathematics learning learning with the concept of doing Sundanese Sundanese games based on themes can be understood by early childhood.